2017
DOI: 10.1016/j.bbr.2017.01.046
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotional inhibitory control in specific internet addiction – an fMRI study

Abstract: h i g h l i g h t s • Higher social anxiety & reduced emotional competence in specific internet addicts. • Longer reaction times in EST for socially anxious words in internet gaming addicts. • Left middle and superior temporal gyrus hypoactivation in internet gaming addicts. • Social words may be less retrievable in semantic storage of internet gaming addicts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 59 publications
(84 reference statements)
1
39
0
Order By: Relevance
“…The BIS-11 correlates of the FC alternations demonstrated that the impairment in the prefrontal-striatal circuits may have an impact on impulsive behavior of IGD subjects. Previous neuroimaging studies reported that functional impairment in the PFC regions was associated with the high impulsivity in IGD ( 37 ). The prefrontal-striatal circuits include a cognitive loop, which mainly connects the caudate and the putamen with prefrontal regions.…”
Section: Discussionmentioning
confidence: 97%
“…The BIS-11 correlates of the FC alternations demonstrated that the impairment in the prefrontal-striatal circuits may have an impact on impulsive behavior of IGD subjects. Previous neuroimaging studies reported that functional impairment in the PFC regions was associated with the high impulsivity in IGD ( 37 ). The prefrontal-striatal circuits include a cognitive loop, which mainly connects the caudate and the putamen with prefrontal regions.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Ding et al () suggested that impaired function of the prefrontal cortex may relate to high impulsivity in adolescents with IA, which may contribute directly to the IA process. Dieter et al () revealed decreased left middle and superior temporal gyrus activation while experiencing socially anxious words in internet gaming addicts. Additionally, risk taking is related importantly to addictive behaviors (Panwar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found decreased left middle and superior temporal gyrus activation during interference of socially anxious words in IGD, possibly indicating social anxiety ( 71 ). A meta-analysis concluded that individuals with IGD are more likely to exhibit impaired response inhibition ( 72 ).…”
Section: Brain Activationmentioning
confidence: 99%